The Use of KitaPad (Kitabah iPad) as a Learning Medium to Improve Arabic Writing Proficiency - Sindha Putri Rahmadani; Muflihah Muflihah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
Writing skills (maharah kitabah) are among the fundamental competencies in learning Arabic ; however, they frequently receive insufficient emphasis in instructional practice. Limited student interest and the scarcity of varied learning media have become major obstacles to achieving optimal results, particularly in writing proficiency. The purpose of this study is to assess the effectiveness of  KitaPad (Kitabah iPad), a learning medium that utilizes visual templates, in improving the writing skills of 10th-grade students. KitaPad was developed to create a more engaging, interactive, and well-structured learning process through the use of iPad technology equipped with visual templates that support students’ cognitive and writing development. The study employed a quantitative approach with a one-group pretest–posttest design, involving one class that received instruction using KitaPad. Data were collected through written tests administered before and after the treatment. The findings revealed a notable increase in students’ post-test scores relative to their pre-test results, indicating that KitaPad successfully enhances writing skills. Hence, technology-based visual media like KitaPad offer substantial potential to enhance student motivation and learning outcomes, particularly in the area of writing proficiency.